Interpreting China's Grand Strategy Past, Present, and Future - Swaine, Michael D. (RAND Corporation, 2000)
China's continuing rapid economic growth and expanding involvement in global affairs pose major implications for the power structure of the international system. To more accurately and fully assess the significance of China's emergence for the United States and the global community, it is necessary to gain a more complete understanding of Chinese security thought and behavior. This study addresses such questions as: What are China's most fundamental national security objectives? How has the Chinese state employed force and diplomacy in the pursuit of these objectives over the centuries? What security strategy does China pursue today and how will it evolve in the future? The study asserts that Chinese history, the behavior of earlier rising powers, and the basic structure and logic of international power relations all suggest that, although a strong China will likely become more assertive globally, this possibility is unlikely to emerge before 2015-2020 at the earliest. To handle this situation, the study argues that the United States should adopt a policy of realistic engagement with China that combines efforts to pursue cooperation whenever possible; to prevent, if necessary, the acquisition by China of capabilities that would threaten America's core national security interests; and to remain prepared to cope with the consequences of a more assertive China.